6(x+9)=-26-4x

Simple and best practice solution for 6(x+9)=-26-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+9)=-26-4x equation:


Simplifying
6(x + 9) = -26 + -4x

Reorder the terms:
6(9 + x) = -26 + -4x
(9 * 6 + x * 6) = -26 + -4x
(54 + 6x) = -26 + -4x

Solving
54 + 6x = -26 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
54 + 6x + 4x = -26 + -4x + 4x

Combine like terms: 6x + 4x = 10x
54 + 10x = -26 + -4x + 4x

Combine like terms: -4x + 4x = 0
54 + 10x = -26 + 0
54 + 10x = -26

Add '-54' to each side of the equation.
54 + -54 + 10x = -26 + -54

Combine like terms: 54 + -54 = 0
0 + 10x = -26 + -54
10x = -26 + -54

Combine like terms: -26 + -54 = -80
10x = -80

Divide each side by '10'.
x = -8

Simplifying
x = -8

See similar equations:

| 8+10x= | | 21-a+4a=6 | | 2+6(7-x)=20 | | [4(x+2)]+9=15 | | (-12x-3)(12x^2-11x+3)= | | 3a^3-4a=-4a^2 | | 6x+5=6x+7 | | (.36x^2)-9x-7000=0 | | 2x^2+23x-8.1=0 | | 18=7(b-1)+4(1-7b) | | [2(x-3)]=10 | | 140=11x+9 | | 4(c+7)=7+c | | -5x+4y=31 | | 4ln+8l=56 | | -4[s+9]=-24 | | 5a-5=4a+2 | | 5(y-1)=3y+5 | | 81x^2+18x+6=0 | | 2[2r+4]=-16 | | [3(x-1)]=15 | | r^2-10r+2=0 | | 8-3.5x=2808 | | 0.9x-0.3(4-x)=6.6 | | 2x-11=y | | 6(3+x)=5(x-6) | | 4a=2(a+2)-12 | | y-3=2(-1+1) | | 7(10)+7(10)+12(10)=360 | | 3+x+5-2x=78 | | 4x(2x-7)=112 | | 3x+5[2-4(x-2)]=x-4 |

Equations solver categories